In vitro anti-platelet potency of ticagrelor in blood samples from infants and children. Issue 3 (September 2015) - Söderlund, Fredrik; Asztély, Anna-Karin; Jeppsson, Anders; Nylander, Sven; Berggren, Anders; Nelander, Karin; Castellheim, Albert; Romlin, Birgitta S.
Abstract Introduction Ticagrelor, a novel platelet inhibitor acting on the ADP-dependent P2Y12 receptor, is currently approved for treating adults with acute coronary syndrome. The effect of ticagrelor in children has not been explored. As a first step, we here evaluate if the in vitro anti-platelet potency of ticagrelor in blood samples from children of different age is different as compared with in blood samples from adults. Materials and Methods Blood samples from 36 healthy children grouped by age (0–2 months, n = 6; 2–6 months, n = 6; 6 months-2 years, n = 6; 2–6 years, n = 10; 6–12 years, n = 8) and 13 adults were collected for in vitro analysis using vasodilator stimulated phosphoprotein phosphorylation (VASP) assay in whole blood and ADP-induced light transmission aggregometry (LTA) in platelet rich plasma. Ticagrelor (0.01 – 10 μmol/L) was added in vitro and its potency was assessed by calculating the concentration that provided 50% inhibition of the maximum response (IC50). Results The in vitro potency of ticagrelor in blood from adults and in blood from children of any age group were comparable, both when analyzed with LTA and with VASP. Conclusions These in vitro results are consistent with the hypothesis that ticagrelor would achieve a comparable anti-platelet effect in children of different ages as in adults at equal plasma exposure.